2022
DOI: 10.1029/2021jd035470
|View full text |Cite
|
Sign up to set email alerts
|

Marine Boundary Layer Decoupling and the Stable Isotopic Composition of Water Vapor

Abstract: Marine boundary layer (MBL) stratocumulus clouds play a crucial role in the climate system, radiatively cooling the Earth through strong reflectance of incoming shortwave radiation compared to the underlying ocean, with comparatively little impact in the longwave portion of the spectrum due to cloud top temperatures that are not significantly different than the surface. These important cloud types are maintained by turbulence driven by cloud top radiative cooling that generates mixing between the oceanic sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
7
2
Order By: Relevance
“…The large-scale environment for coupled Sc exhibited a similar pattern, with the Azores surface high located over Graciosa Island (Figure S4a in Supporting Information S1 and Galewsky et al, 2022, their Figure 5). Contrary to our findings, Galewsky et al (2022) showed that the Azores surface high for decoupled cases was shifted to the northeast. The center of the Azores surface high for this study moved toward the southwest even though we consider a longer time period (October 2015 to September 2017; Figures S4a and S4b in Supporting Information S1).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The large-scale environment for coupled Sc exhibited a similar pattern, with the Azores surface high located over Graciosa Island (Figure S4a in Supporting Information S1 and Galewsky et al, 2022, their Figure 5). Contrary to our findings, Galewsky et al (2022) showed that the Azores surface high for decoupled cases was shifted to the northeast. The center of the Azores surface high for this study moved toward the southwest even though we consider a longer time period (October 2015 to September 2017; Figures S4a and S4b in Supporting Information S1).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, Galewsky et al. (2022) showed that the Azores surface high for decoupled cases was shifted to the northeast. The center of the Azores surface high for this study moved toward the southwest even though we consider a longer time period (October 2015 to September 2017; Figures S4a and S4b in Supporting Information ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, several recent studies have questioned the assumed role of SST and wind speed on the controls of nonequilibrium fractionation based on water vapor d ‐excess observations (Bonne et al., 2019 ; Pfahl & Sodemann, 2014 ; Pfahl & Wernli, 2008 ; Steen‐Larsen et al., 2014 , 2015 ; Uemura et al., 2008 ). Other studies argued that water vapor d ‐excess above the ocean surface may not be influenced solely by ocean surface evaporative conditions, namely RH and SST, but also by the coupling between the marine boundary layer (MBL) and the free troposphere (Benetti et al., 2018 ; Galewsky et al., 2022 ) as well as by air–sea interactions during cold and warm advection (Thurnherr et al., 2021 ). Consequently, it can be concluded that a substantial uncertainty exists on the magnitude of nonequilibrium fractionation during evaporation in real‐environmental conditions and, still, no agreement exists on the controls of nonequilibrium fractionation by SST and wind speed (e.g., Gonfiantini et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%